2010
DOI: 10.1002/anie.200906342
|View full text |Cite
|
Sign up to set email alerts
|

Modular Synthesis of 1,2‐Diamine Derivatives by Palladium‐Catalyzed Aerobic Oxidative Cyclization of Allylic Sulfamides

Abstract: Allylic sulfamides undergo efficient aerobic oxidative cyclization at room temperature, mediated by a new Pd catalyst system consisting of 5% Pd(TFA)2/10% DMSO in THF. The synthetic utility of these reactions is enhanced by several features: (1) the sulfamide substrates are accessible in multi-gram scale from the corresponding allylic and primary amines, (2) the cyclic sulfamide products are readily converted to the corresponding 1,2-diamines upon treatment with LiAlH4, and (3) substrates derived from chiral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(16 citation statements)
references
References 54 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…Encouraged by this result, we further systematically optimized the reaction conditions to improve the conversion of the reaction and inhibit the formation of benzoyl indoles (Figure 2c). It was reported that either aminopalladated or π-allyl Pd intermediates would be generated in palladium-catalyzed allylic C-H oxidation reaction with the usage of ambident O/N nucleophiles [37][38][39]. Our method can avoid the generation of the π-allyl Pd intermediates and obtain corresponding N-benzoyl indoles.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Encouraged by this result, we further systematically optimized the reaction conditions to improve the conversion of the reaction and inhibit the formation of benzoyl indoles (Figure 2c). It was reported that either aminopalladated or π-allyl Pd intermediates would be generated in palladium-catalyzed allylic C-H oxidation reaction with the usage of ambident O/N nucleophiles [37][38][39]. Our method can avoid the generation of the π-allyl Pd intermediates and obtain corresponding N-benzoyl indoles.…”
Section: Resultsmentioning
confidence: 97%
“…In this context, our strategy is to use commercially available and inexpensive catalyst Pd(OAc) 2 and oxidant benzoquinone (BQ) for C-H functionalization to construct substituted N-benzoyl indoles (Figure 2c). It was reported that either aminopalladated or π-allyl Pd intermediates would be generated in palladium-catalyzed allylic C-H oxidation reaction with the usage of ambident O/N nucleophiles [37][38][39]. Our method can avoid the generation of the π-allyl Pd intermediates and obtain corresponding N-benzoyl indoles.…”
Section: Introductionmentioning
confidence: 97%
“…6). 11 Starting materials were synthesized in a two-step sequence from mono-amine precursors. Oxidative cyclization occurred in good yields and with excellent diastereoselectivity (oen >30 : 1) using the reagent combination of 5 mol% Pd(TFA) 2 , 10 mol% DMSO, 20 mol% NaOBz in THF under 1 atmosphere of O 2 .…”
Section: Sulfamide Tethered Aza-wacker Cyclization (2010)mentioning
confidence: 99%
“…Endgame of the melinonine and strychnoxanthine synthesis.8084 | Chem. Sci., 2020,11,[8073][8074][8075][8076][8077][8078][8079][8080][8081][8082][8083][8084][8085][8086][8087][8088] This journal is © The Royal Society of Chemistry 2020Chemical Science Minireview Open Access Article. Published on 21 July 2020.…”
mentioning
confidence: 99%
“…However, the palladium-catalyzed extremely labile allylic C–H functionalization of phenolic, aniline, or aliphatic amines is unknown. Furthermore, the underlying mechanism of allylic C–H functionalization is highly ambiguous due to the competitive allylic C–H bond cleavage/π-allyl Pd complex formation versus olefin isomerization/nucleopalladation/β-hydride elimination pathways (Scheme d) . However, the latter olefin isomerization relay is extremely fascinating for the site-selective remote functionalization .…”
mentioning
confidence: 99%